Epidemiology of pediatric cardiopulmonary resuscitation - Shimoda-Sakano,Tania Miyuki (2020)
Abstract Objective: To analyze the main epidemiological aspects of prehospital and hospital pediatric cardiopulmonary resuscitation and the impact of scientific evidence on survival. Source of data: This was a narrative review of the literature published at PubMed/MEDLINE until January 2019 including original and review articles, systematic reviews, meta-analyses, annals of congresses, and manual search of selected articles. Synthesis of data: The prehospital and hospital settings have different characteristics and prognoses. Pediatric prehospital cardiopulmonary arrest has a three-fold lower survival rate than cardiopulmonary arrest in the hospital setting, occurring mostly at home and in children under 1 year. Higher survival appears to be associated with age progression, shockable rhythm, emergency medical care, use of automatic external defibrillator, high-quality early life support, telephone dispatcher-assisted cardiopulmonary resuscitation, and is strongly associated with witnessed cardiopulmonary arrest. In the hospital setting, a higher incidence was observed in children under 1 year of age, and mortality increased with age. Higher survival was observed with shorter cardiopulmonary resuscitation duration, occurrence on weekdays and during daytime, initial shockable rhythm, and previous monitoring. Despite the poor prognosis of pediatric cardiopulmonary resuscitation, an increase in survival has been observed in recent years, with good neurological prognosis in the hospital setting. Conclusions: A great progress in the science of pediatric cardiopulmonary resuscitation has been observed, especially in developed countries. The recognition of the epidemiological aspects that influence cardiopulmonary resuscitation survival may direct efforts towards more effective actions; thus, studies in emerging and less favored countries remains a priority regarding the knowledge of local factors.